IMPLIKASI CALON TUNGGAL PILKADA KABUPATEN TASIKMALAYA TERHADAP KUALITAS DEMOKRASI DAERAH: Implications of a Sole Candidate in the Tasikmalaya Local Election on the Quality of Regional Democracy - Habibi, Habibi (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2018)
AbstractThe general election is activities of citizens, which are held every five years. In this activity the General Election Commission (KPU) as the organizer prepares all the needs to run elections based on related regulations, which has been changed several times. In former regulation, there is no stipulation on independent candidate nor single-candidate local leader election. Political parties has roles to fulfil, two of them are political education and regeneration of political cadres. There are 17 political parties in Tasikmalaya but none of them nominate their best cadres. This article tries to describe the implications of single candidate in head of regency election to political parties. By applying qualitative research and empirical-juridical approach, it shows that there was an agreement between political parties in 2015 Tasikmalaya head of regency election to advocate single candidate, while independent candidates as alternative choice for people should fulfil various requirements that hindered their candidacies. Normatifly this phenomena has legal base with the Constitutional Court Decision No. 100/PUU/XIII/2015 that granted Effendi Ghazali’s plead, but substantially damaging democracy. It is feared to occur that a candidate who has strong financial backup influences political elite to support single candidacy. This condition can also discourage political partied to generate new cadres that has great capabilities to compete in general elections.Keywords:head of regency election, single candidate, political party Abstrak Pemilihan Umum adalah kegiatan warga Negara yang diselenggarakan setiap lima tahun sekali, dalam kegiatan ini KPU sebagai lembaga penyelenggara mempersiapkan segala kebutuhan untuk berjalannya pemilihan. Regulasi UU yang berkaitan dengan pemilihan kepala daerah sudah mengalami beberapa perubahan. UU sebelumnya tidak mengatur calon tunggal dalam konstestasi pilkada. Munculnya fenemona calon tunggal mendorong Mahkamah Konstitusi mengeluarkan putusan untuk dipersilahkannya calon tunggal. Uniknya salah satu tugas peran dan fungsi partai politik adalah edukasi politik, kaderisasi, lembaga yang kompetitif dalam pilkada, tidak mau mencalonkan dari kader-kader terbaiknya, padahal jumlah partai saat ini di Kabupaten Tasikmalaya sudah mencapai 17 partai. Tujuan tulisan ini adalah untuk memaparkanimplikasi calon tunggal kepala daerah Kabupaten Tasikmalaya terhadap partai politik. Dengan pendekatan yuridis empiris, hasil penelitian menunjukkan bahwa terdapat kesepakatan antar parpol pada masa pemilu tahun 2015 di Kabupaten Tasikmalaya untuk mengusung satu pasangan saja. Adapun calon perseorangan sebagai pilihan alternatif dihadapkan pada persyaratan yang menghambat proses pencalonan. Secara normatif hal tersebut tidak menjadi masalah dengan munculnya Putusan Mahkamah Konstitusi No. 100/PUU/XIII /2015, namun secara substansi demokrasi hal tersebut berdampak buruk. Dikhawatirkan muncul kecenderungan pasangan calon yang mempunyai modal besar untuk membayar elit-elit politik agar dapat mempengaruhi munculnya calon tunggal serta mengurangi kemampuan organisasi dalam mencetak kader dan pemimpin yang mampu bersaing di arena pemilu.Kata kunci: Pemilihan Kepala Daerah, kandidat tunggal, partai politik.